Tussen katedrale en kastele: Oor die teologies-politieke probleem - Goosen, Daniël P. (HTS teologiese studies, 2009)
Flanked by cathedrals and castles: Theology and its political problemThis article is a reflection on the theological-political problem (i.e. the question about the relationship between religion and politics) in modern society. It presupposes that this problem was created by modernism. Because modernism distinguished in a reductive fashion between religion and politics, modern society was left with the burning question of how to mediate between them. The first part of the article focuses on a critical appraisal of the modern distinction. In different sub-sections it is argued that the modern distinction led to a reduction in meaning of both the religious and the political. However, the modern distinction cannot be maintained. Contrary to the modern distinction it is argued that the political is always already infiltrated by the theological. Modernism cannot deliver on its promises. In the concluding section the argument is raised that the theological-political problem can be addressed if we as are willing to listen to the voice of tradition. According to tradition, desire (eros) reaches out from the lowest to the highest levels of reality. The relationship between the political and the theological is inscribed within the erotic curve of desire. While eros reaches out to and also finds fulfilment in active political participation, this does not represent the end of its journey. Eros even reaches further, to the transcendent realms of philosophical contemplation and theological wisdom. In the concluding sections it is argued that both the political and the religious can again be experienced as glorious phenomena due to their erotic mutuality. Their mutuality is not (pace modernism) an argument against their own integrity, but precisely an argument in favour thereof. Die moderne wêreld staan in spanning met alle stede uit die oudheid, met alles wat kultuur verteenwoordig, met alles wat tot ’n stad behoort.(Charles Péguy)